Rusty sink of rhizodeposits and associated keystone microbiomes. (August 2020) - Jeewani, Peduruhewa H.; Gunina, Anna; Tao, Liang; Zhu, Zhenke; Kuzyakov, Yakov; Van Zwieten, Lukas; Guggenberger, Georg; Shen, Congcong; Yu, Guanghui; Singh, Bhupinder Pal; Pan, Shaotong; Luo, Yu; et al.
Abstract: Iron hydroxides serve as an efficient 'rusty sink' promoting the stabilization of rhizodeposits into soil organic carbon (SOC). Our work aimed to understand the physicochemical and microbial mechanisms promoting rhizodeposit (rhizo-C) stabilization as influenced by goethite (α-FeOOH) or nitrogen (N), using 13 C natural abundance methodologies and DNA sequencing, in the rhizosphere of maize ( Zea mays L.). The addition of N fertilizer to soil increased the mineralization of both rhizo-C and SOC, while amendment with α-FeOOH decreased rhizo-C derived CO2 and lowered the rhizosphere priming effect by 0.57 and 0.74-fold, respectively, compared to the control soil. This decrease resulted from the co-precipitation of rhizo-C at the reactive α-FeOOH surfaces as Fe-organic matter complexes (FeOM), which was 10-times greater than the co-precipitation on short-range ordered minerals. The highest portion of rhizo-C (67% of the total accumulated in soil) was protected within macroaggregates (>2 mm). Carbon overlapped with α-FeOOH mainly in >2 mm aggregates, as shown by HRTEM-EDS imaging, suggesting that α-FeOOH associated rhizo-C stimulated aggregate formation. Random forest analysis confirmed that the stabilization of rhizo-C was controlled mainly by physiochemical binding within FeOM complexes and macroaggregates. Rhizo-C mineralization was regulated by the keystone microbiome: Paucimonas (β-Proteobacteria) being an r-strategist with rapid growth under soil without nutrient limitation (N treated) and Steroidobacter (Actinobacteria) with branched filaments that can access C and nutrients under oligotrophic conditions (goethite enriched soil). Two-way orthogonal partial least squares analysis revealed that the rhizosphere priming effect was facilitated mainly by the same genera, most likely due to co-metabolism. The genera belonging to Acidimicrobiaceae (Actinobacteria), Cryptococcus and Cystofilobasidium (Basidiomycota) were positively correlated with the accumulation of rhizo-C in the >2 mm aggregate size, which might due to their high affinity towards α-FeOOH and contribution to the development of aggregation via filamentary structures that interact with microaggregates. We suggest that rhizodeposit stabilization in soil was balanced by microbial mineralization and abiotic associations with the "rusty sink" and organisms with branched filaments contributing to the development of aggregation. Highlights: α-FeOOH is a 'rusty sink' for rhizodeposited-C (Rhizo-C) via Fe bound complexes (FeOM), stimulating aggregate formation. Rhizo-C mineralization and rhizosphere priming decreased in soil amended with α-FeOOH. The rhizosphere microbial community was modulated by changed edaphic variables by α-FeOOH (e.g. rhizo-C availability). Stabilization of rhizo-C in aggregates and FeOM were associated with Actinobacteria and Basidiomycota.